(untitled) (Journal of Pharmaceutical Negative Results, 2023)
People focus more on aesthetics and lifestyle in the current society. Since consumers are spending more money on cosmetics, marketers feel compelled to pay extra attention to this industry. In addition, there is fierce rivalry in this industry to satisfy customer desire. The study's goal is to investigate the factors that influence brand loyalty among consumers of cosmetics in Chennai, an Indian metropolis. Brand loyalty, customer happiness, brand experience, perceived quality, pricing, brand awareness, brand credibility, and brand reputation are the components taken into consideration in this study. 688 respondents completed a structured survey on a Likert scale with a maximum of five points. Correlation analysis and correspondence analysis were used to analyse the survey-collected data. According to the findings, there is a correlation between the brand loyalty research components and the effect of educational background and favourite store type on brand loyalty levels.